Flowers in the Wall Truth and Reconciliation in Timor-Leste, Indonesia, and Melanesia - Webster, David (Global Indigenous Issues, 2018)
What is the experience of truth and reconciliation? What is the purpose of a truth commission? What lessons can be learned from established truth and reconciliation processes? Flowers in the Wall explores the experience of truth and reconciliation Southeast Asia and the Southwest Pacific, with and without a formal truth commission. Although much has been written about the operational phases of truth commissions, the efforts to establish these commissions and the struggle to put their recommendations into effect are often overlooked. Examining both the pre- and post-truth commission phases, this volume explores a diversity of interconnected scholarship with each chapter forming part of a concise narrative. Well-researched and balanced, this book explores the effectiveness of the truth commission as transnational justice, highlighting its limitations and offering valuable lessons Canadians, and all others, facing similar issues of truth and reconciliation. With Contributions By: Sarah Zwierzchowski, Geoffrey Robinson, Pat Walsh, Jacqueline Aquino Siapno, Laurentina "mica" Barreto Soares, Jess Augustin, Fernanda Borges, Maria Manuela Leong, Baskara Wardaya, Bernd, Gatot Lestario, Lia Kent, Rizki Amalia Affiat, Arianto Sangadji, Jenny Munro, Todd Biderman, Julian Smythe, Terry M. Brown, Edmund McWilliams, Betty Lina Gigisi, and Maggie Helwig